2021
DOI: 10.1093/neuros/nyab294
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative HbA1c > 8% Is Associated With Poor Outcomes in Lumbar Spine Surgery: A Michigan Spine Surgery Improvement Collaborative Study

Abstract: BACKGROUND Preoperative hemoglobin A1c (HbA1c) is a useful screening tool since a significant portion of diabetic patients in the United States are undiagnosed and the prevalence of diabetes continues to increase. However, there is a paucity of literature analyzing comprehensive association between HbA1c and postoperative outcome in lumbar spine surgery. Objective To assess the prognostic value of preoperative HbA1c > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…At present, most studies have confirmed that glycosylated hemoglobin ≥6.5% (≥48 mmol/mol) can irremediable long-term risk for diabetic complications and mortality ( 19 ). Lim et al ( 20 ) analyzed 4,778 patients and showed that patients with preoperative hemoglobin A1c (HbA1c) > 8% were more likely to experience postoperative complication; indeed, in our study, glycosylated hemoglobin ≥6.5% was an independent risk factor affecting the satisfaction of OTCF patients, indicating that controlling HbA1C level <6.5% was beneficial. What's more, a systematic review showed that preoperativeHbA1c > 7.5 mg/dl was associated with an increased risk of reoperation or infection after spine surgery ( 21 ).…”
Section: Discussionsupporting
confidence: 58%
“…At present, most studies have confirmed that glycosylated hemoglobin ≥6.5% (≥48 mmol/mol) can irremediable long-term risk for diabetic complications and mortality ( 19 ). Lim et al ( 20 ) analyzed 4,778 patients and showed that patients with preoperative hemoglobin A1c (HbA1c) > 8% were more likely to experience postoperative complication; indeed, in our study, glycosylated hemoglobin ≥6.5% was an independent risk factor affecting the satisfaction of OTCF patients, indicating that controlling HbA1C level <6.5% was beneficial. What's more, a systematic review showed that preoperativeHbA1c > 7.5 mg/dl was associated with an increased risk of reoperation or infection after spine surgery ( 21 ).…”
Section: Discussionsupporting
confidence: 58%
“…Despite the heterogeneity of outcome measures, results can be parsed based on preoperative HbA1c cutoff values ranging from 6.1% to 8.0%, utilized by 14 of 22 included studies, with 8.0% being the most frequently endorsed. Several studies have assessed preoperative HbA1c using a threshold of 8.0% and found increased likelihood for postoperative complications associated with HbA1c above this level 17,18,31 . This same cutoff is supported by the results of this meta-analysis, which demonstrated that patients with preoperative HbA1c over 8.0% have a 1.85 relative risk of developing postoperative complications compared to those with HbA1c under 8.0%.…”
Section: Discussionsupporting
confidence: 57%
“…Several studies have assessed preoperative HbA1c using a threshold of 8.0% and found increased likelihood for postoperative complications associated with HbA1c above this level. 17,18,31 This same cutoff is supported by the results of this meta-analysis, which demonstrated that patients with preoperative HbA1c over 8.0% have a 1.85 relative risk of developing postoperative complications compared to those with HbA1c under 8.0%. Although an HbA1c above 8.0% is associated with an increased risk of overall complications, further research is needed to determine whether this is the optimal threshold value.…”
Section: Discussionmentioning
confidence: 54%
“…Preoperative short-term glucose control has been associated with wound complications [ 24 ], myocardial injury after noncardiac surgery, and 30-day mortality [ 25 ]. Likewise, preoperative long-term glucose control has been associated with postoperative complications and long-term survival [ 26 , 27 ]. There is no consensus on which strategy of perioperative glycemic control is better for improving perioperative complications of patients undergoing surgery [ 28 ].…”
Section: Discussionmentioning
confidence: 99%